The dynamics of the cellular composition of urine sediment in conditions of an artificial bladder - Savchuk, R. V.; Kostyev, F. I.; Dekhtiar, Y. M.; Zhukovsky, D. A.; Nasibulin, B. A.; Kuznietsov, D. A. (Journal of Education, Health and Sport, 2017)
Aim. The evaluation of the urine cytological profile in the dynamics of adaptation of the orthotopic bladder to the functional properties of the urinary reservoir and determination of the connection between the cellular composition of the urine with the functional role of the formed from the intestinal fragment neocyst in experimental conditions and in humans. Materials and methods. The material in experimental study were the results of a cytological study of the urine sediment obtained from 21 female pigs (mini-pigs). The portion of urine had received in experimental animals one month after orthotopic ileocystoplasty, 6 months and 1 year later and prepared as smear from the resulting precipitate. The level of lymphocytes, neutrophils, erythrocytes, as well as the superficial, intermediate and basal epitheliocytes evaluated during study. An analysis of the cell composition of centrifugal smears from the neocyst were performed in 21 patients with bladder cancer undergoing cystectomy and the formation of an orthotopic bladder, at various periods after surgery, from 3 months to 5 years. The preparation of a centrifugal sediment and the subsequent production of smears carried out as well as experimental animals. Results and conclusions. The results of study showed that the formation of an artificial bladder in experimental animals with a fragment of the ileum changes the composition of the cells of the urinary sediment mucosa. These changes consist of an increase in the content of red blood cells, a decrease in the number of lymphocytes and neutrophils and change in the number of epithelial cells. The cellular composition of the sediment changes with the increasing duration of the postoperative period and manifests by reduction and even disappearance of erythrocytes in smears. The level of lymphocytes and neutrophils is close to those observed in intact animals. The content and ratio of epithelial cells also approached to experimental animals. The structure of the organ and its function are closely related and there can be the adaptation of the tissues of the intestinal wall to new conditions. It may have accompanied the topography of the location of the vessels, which reduces the likelihood diapedetic yield of erythrocytes. It can be assumed that the lymphoid follicles of the mucosa of the intestinal wall are atrophied and the mucosal protection approaches that observed in the intact bladder. It is also possible to transform the epithelium of the mucosa, which changes the composition of epithelial cells in the sediment. The study of the urine sediment centrifuge in the dynamics of functioning of neobladder formed from the ileum wall showed similar dynamics of its cellular composition. The same adaptive adjustment processes take place as in the experimental animals. One of the factors of oncogenesis is the disregulatory pathology of regeneration processes. It allows to establish that a regular assessment of the composition of urine centrifuge cells will allow diagnosing possible shifts in the regulation of regeneration processes in patients after formation of artificial bladder. It is necessary for oncological control of local recurrence and early detection of urothelial cancers of the upper urinary ways.